Catheter Ablation for the Management of Atrial Fibrillation: An Update of the Literature - Shahana Hussain; Catrin Sohrabi; Rui Providencia; Syed Ahsan; Nikolaos Papageorgiou (Life, 2023)
Catheter ablation has been shown to be more effective at maintaining sinus rhythm and improving quality of life when compared to antiarrhythmic drugs. Radiofrequency and cryoablation are two effective methods. However, catheter-only ablation strategies have not consistently produced high success rates in treating longstanding and persistent AF patients. The emerging treatment of choice for such cases is hybrid ablation, which involves a multidisciplinary and minimally invasive approach to achieve surgical ablation of the direct posterior left atrial wall in combination with endocardial catheter ablation. Studies have shown promising results for the hybrid approach when compared with catheter ablation alone, but it is not without risks. Large and randomised studies are necessary to further evaluate these strategies for managing AF.